Optimization of Vice Manufacturing Cost Using VDI 2222: Balancing Strength, Weight, and Cost - Fidelis Gigih Triatmaja, Fidelis Gigih Triatmaja; Christian Unsu Taolin; Devano Fajar Hermawan; Utomo, Archi Kun Cahyo (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2025)
This study presents the redesign of a machine vice used in the Great D1 universal grinding machine, to improve manufacturability, reduce weight, and minimize production costs. The redesign process followed the structured VDI 2222 product development methodology, which includes four phases: task clarification, conceptual design, embodiment design, and detailed design. Through a systematic evaluation of design variants using technical and economic criteria, the final concept was selected and refined using CAD modeling and CNC-oriented manufacturing strategies. The resulting design maintained functional performance while achieving a weight reduction of over 30% and a machining time reduction of more than 50%. Material cost savings were also achieved by using a hybrid structure, with cast iron for the base and aluminum for the movable components. Overall, the total production cost was reduced by approximately 41.8%. In addition to economic benefits, ergonomic improvements such as modular part construction and improved accessibility were realized. These outcomes demonstrate that the structured application of VDI 2222 enables effective redesign of legacy equipment and provides measurable improvements in cost, usability, and production efficiency.